Topography of the blood vessels in the hilum of the kidney of Myrmecophaga tridactyla - Souza, W. M. [UNESP]; Miglino, M. A.; Arantes, I. G.; Nascimento, A. A. (My University, 1991)
The study was undertaken in 10 formol-imbibed kidneys of great anteater (Myrmecophaga tridactyla). After the dissection the following characteristics were showed: kidney blood vessels are distributed in 2 different sites, namely hilar and extrahilar, amounting 3 to 6 in the right side 3 to 7 in the left side. Arterial branches in extrahilar region range from 1 to 2 in both sides and in hilar region they present from 1 to 4 in the right and 1 to 2 in the left. Venous roots occur in 1 to 2 vessels in the right and 1 to 3 vessels in the left, occupying only the hilar region, except one case where it was present in the right side.